Blockchain as a new paradigm: reflections from a technologicalinstitutional perspective - Salinas, Javier (2021)
Blockchain (BC) technology combines cryptography, asymmetric mathematics, open-source software, peerto-peer computer networks, consensus algorithms, and incentive mechanisms that allow users to reach agreement on the state of a shared ledger. To understand the transformational scope of BC technology, founding principles and the solution to the economic problem of trust are used. It is discussed that BC economics can be understood beyond the analysis of a general-purpose technology, since it can also be understood as an evolutionary instance of “metainstitutional” technology. This essay presents reflections based on a technologicalinstitutional perspective that is derived from several contributions to the literature of various authors who write about different perspectives and types of technology regarding BC. These reflections are carried out, in part, by conceptualizing and exemplifying, with real use cases, how BC technology allows capturing “static” and/or “dynamic” efficiency; detailing the characteristics for its consideration as a new market institution; and exploring new governance mechanisms (i.e., cooperation and coordination) based on BC.